2020
DOI: 10.1177/0734242x20922588
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and characterization of the municipal solid waste for sustainable waste management in newly formed municipalities of Nepal

Abstract: This study was conducted to set up a new reference line for municipal solid waste quantification and characterization in the least urbanized cities of a developing nation. A survey was run to collect baseline data from 60 new municipalities of Nepal. The study covered a sample size of 3300 households, 600 institutions and 600 commercial establishments in those municipalities. The municipalities were further stratified according to geographical location, the degree of urbanization, household expenditure and pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Household waste, agriculture waste, industrial waste, hotel and, grocery waste has been the major source of the waste; however, household waste is a major contributor to municipal solid waste in developing countries like Nepal. It is estimated that the waste generated from the household accounts for about 65%- 70% of total municipal solid waste in Nepal (Pathak et al 2020 ). Furthermore, this study found that the amount of household waste has been increased during this pandemic because of medical masks, tissues, and gloves.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Household waste, agriculture waste, industrial waste, hotel and, grocery waste has been the major source of the waste; however, household waste is a major contributor to municipal solid waste in developing countries like Nepal. It is estimated that the waste generated from the household accounts for about 65%- 70% of total municipal solid waste in Nepal (Pathak et al 2020 ). Furthermore, this study found that the amount of household waste has been increased during this pandemic because of medical masks, tissues, and gloves.…”
Section: Resultsmentioning
confidence: 99%
“…The act seeks to uphold a sustainable and stable atmosphere by reducing the detrimental impact of solid waste on public health and the ecosystem (Asian Development Bank 2013 ). Recently, Pathak et al conducted an SWM baseline study to quantify MSW and its composition and to compile reliable information on the state of MSWM in the 60 newly formed municipalities of Nepal (Pathak et al 2020 ). The average composition of waste in different ecological regions is varied from organic wastes, plastics, paper-products, glasses, metals, textiles, rubber-leather, and other different compositions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upsurge in the rate of solid waste generation is an unavoidable repercussion of production and consumption activities, and urbanization expansion consequent upon population growth in developing countries ( Gallardo et al, 2018 ; Pathak et al, 2020 ). Sustainable waste management has been prioritized in South Africa to ensure that all generated waste does not necessarily end up in landfills, because most landfill sites are reported to be running out of space for waste disposal.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we have proposed the CTF under different infectious waste management scenarios and recommended its implementation modality for all the HFs of Nepalgunj SMC as a case study. As accurate estimates on waste generation and waste characteristics are crucial to implement proper waste management strategies or to optimise the design of the required waste management infrastructure and facilities (Pathak et al, 2020), first, we quantified the total amount of HCW, its composition and estimated the amount of infectious waste to be treated in the health facilities of Nepalgunj SMC. Second, we explored the existing scenarios for the capacity assessment and implementation modality of CTF to treat infectious HCW.…”
Section: Introductionmentioning
confidence: 99%